A new approach to travelling wave solution of a fourth-order semilinear diffusion equation - İnç, Mustafa; Cherruault, Y (Emerald Group Publishing Limited, 2003)
A decomposition method is implemented for solving travelling wave solutions of a fourth-order semilinear diffusion equation.
Keywords: cybernetics; polynomials